Mossy touch table / Nur Fatin Aniesya Azizul Aziz - Azizul Aziz, Nur Fatin Aniesya (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
The creation of the “Mossy Touch Table” aims to apply the texture of moss onto a piece of furniture for people to use at home that can alleviate their levels of stress, specifically for people that have limited leisure time and are unable to go outside often. It aims to address the ongoing issue of how most modern homes have limited space, which leads to the need to utilize space when furnishing a living space. Not only that, but most of these homes no longer have much connection to nature. Therefore, the “Mossy Touch Table” allows us to bring in a little piece of nature into our homes without sacrificing neither space nor utility. Moss is space efficient, with no need for a large growing area, while also being able to thrive with low-maintenance, making it the perfect plant for people with space and time constraints. Moss does not need to be watered and prefers to be out of direct sunlight, making it ideal to be kept indoors. Paired with it’s non-allergenic properties and fluffy texture, moss can be great for haptic people's tactile needs. Effortlessly add a little greenery in your personal workspace with the “Mossy Touch Table”.